Antioxidant Activity of Gamat (Stichopus variegatus) and Milk Sea Cucumbers (Holothuria fuscocinerea) from the Thousand Islands National Park Waters - Muhammad Septian Azhar Siregar; Eri Bachtiar; Atikah Nurhayati; Muhammad Wahyudi Lewaru (Journal of Aquaculture and Fish Health, 2023)
The frequent use of synthetic antioxidant compounds can cause degenerative diseases, especially consumers, so that natural antioxidant compounds are needed to reduce the risk of disease. One of the biotas that may contain potential as natural antioxidants is sea cucumber. Sea cucumbers are marine invertebrates that have therapeutic properties whose bioactive content has the potential as antioxidants. Thus, this study aims to determine the potential of two species of sea cucumber (Stichopus variegatus and Holothuria fuscocinerea) as natural antioxidant candidates as an alternative to synthetic antioxidants by knowing the bioactive content and analyzing the antioxidant activity of the sample. The research was started from April 1 to September 29, 2021 with methods including sampling in the waters of the Thousand Islands National Park, extraction, antioxidant testing, testing for total compound content, and data analysis on sample extracts of S. variegatus and H. fuscocinerea. The results of the DDPH antioxidant test and β-carotene bleaching assay after the one-way ANOVA test showed that the antioxidant activity value was P < 0.05, which means that there was a significant difference in sample concentration on antioxidant activity. In the method and -carotene bleaching assay, the sample extracts of S. variegatus and H. fuscocinerea were 46.37% and 45.75%, respectively. Based on the value of the antioxidant test results and bioactive content, it can be concluded that the sample extracts of S. variegatus and H. fuscocinerea have very weak antioxidant activity so that they cannot be used as alternative natural antioxidants to replace synthetic antioxidants.